Clinical-epidemiological characterization of tuberculosis in the Cumanayagua Municiality. Cienfuegos Province. 2007-2017 - Narciso Águila Rodríguez; Hilda María Delgado Acosta; Delfín Rodríguez Buergo; Lizette Rodríguez Fernández; Rosario Gutiérrez Castro; Eneida Bravo Polanco (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Introduction: It is a challange to eliminate tuberculosis in Cuba. Objective: to characterize clinically and epidemiologically pacients with tuberculosis. Methods: observational descriptive research which included 24 cases reported with tuberculosis in Cumanayagua from 2007 to 2017. Tha variables analized were: year of diagnosis, classification according to the type of tuberculosis (pulmonary or extra-pulmonary), Age, sex, place of diagnosis, occupation, community, health area, associated risk factors, signs and symptoms. Data was collected from the chronological series and epidemiological histories existing at the Municipal Units of Hygiene and Epidemilogy in the municipality. Data processing was done by excell and percentages and incidence rate were used. Results: the highest rate of the disease presented in 2013. The highest number of cases was reported from 55 to 59 years old with 9 cases. Patients with positive basiloscopy with a 66,7 %. A 62,5 % was diagnosed in the second level of care. The male sex, retired and agriculture workers predominated. The most frequent risk factors were tabaquism and alcoholism. The most frequent symptoms were cough, loss of weight, asthenia and fiver. Conclusion: tuberculosis at the Municipality of Cumanayagua presented according to the clinical and epidemiological characteristics described in the literature reviewed; there were difficulties in the opportunity of diagnosis at the first care level.